Study on employee satisfaction of Bank Asia Ltd; CDA Avenue Branch, Chittagong - Sultana, Afroza (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.